Dietary supplements and the promotion of muscle growth with resistance exercise - Kreider, R. B. (Sports Medicine, 1999)
Nutritional strategies of overfeeding, ingesting carbohydrate/protein before and after exercise, and dietary supplementation of various nutrients [e.g. protein, glutamine, branched-chain amino acid, creatine, leucine, beta-hydroxy beta-methyl-butyrate (beta-HMB), chromium, vanadyl sulfate, boron, prasterone (dehydroepi-androsterone [DHEA]) and androstenedione] have been purported to promote gains in fat-free mass during resistance training. Most studies indicate that chromium, vanadyl sulfate and boron supplementation do not affect muscle growth. However, there is evidence that ingesting carbohydrate/protein prior to exercise may reduce catabolism during exercise and that ingesting carbohydrate/protein following resistance-exercise may promote a more anabolic hormonal profile. Furthermore, glutamine, creatine, leucine, and calcium beta-HMB may affect protein synthesis. Creatine and calcium beta-HMB supplementation during resistance training have been reported to increase fat-free mass in athletic and nonathletic populations. Prasterone supplementation has been reported to increase testosterone and fat-free mass in nontrained populations. However, results are equivocal, studies have yet to be conducted on athletes, and prasterone is considered a banned substance by some athletic organisations.